ANALISIS PENGARUH PENGETAHUAN INVESTASI, TEKNOLOGI KEUANGAN, EFIKASI KEUANGAN DAN LITERASI KEUANGAN TERHADAP MINAT INVESTASI SAHAM MAHASISWA STUDI PADA MAHASISWA PERGURUAN TINGGI DI KOTA SEMARANG - Faizah, Nur Lailatul; Sihwahjoeni, Sihwahjoeni; Safriliana, Retna (STIE PENA, 2025)
This study aims to analyze the effect of investment knowledge, financial technology, financial self-efficacy, and financial literacy on students’ interest in stock investment. Conducted among university students in Semarang City, Indonesia, the research applies a quantitative method using a survey distributed to 100 respondents selected through convenience sampling. The data were analyzed using multiple linear regression. The findings indicate that all four independent variables—investment knowledge, financial technology, financial self-efficacy, and financial literacy—positively influence students’ interest in stock investment. These results highlight that students with better understanding of investment principles, who utilize digital financial platforms, possess confidence in managing personal finances, and demonstrate higher levels of financial literacy are more inclined to invest in stocks. Grounded in the Theory of Planned Behavior, this study emphasizes that internal attitudes and perceived behavioral control significantly affect investment intention. The research contributes to the growing literature on youth investment behavior in emerging markets and offers practical implications for financial educators, policy makers, and fintech developers to foster early investment habits. Enhancing financial knowledge and access to digital tools among students is crucial to promoting a financially literate and investment-savvy generation.Keywords: Investment Knowledge, Financial Technology, Financial Self-Efficacy, Financial Literacy, Students’ interest in stock investment